The Behavioral Finance of the Digital Gold Market: Heuristics, Overconfidence Bias, and Market Sentiment - Agung Pangestu Prihanto; Asep Risman (Universitas Hayam Wuruk Perbanas, 2025)
This study aims to analyze the effect of heuristic and overconfidence biases on investment decision-making through market sentiment. This study was conducted on the digital gold market which has never existed in previous studies, this study also uses market sentiment as a mediating variable. The study population consists of 5,628 investors in the digital gold market at JFX, with a sample of 200 respondents obtained using the convenience sampling technique. The data analysis method employed is Structural Equation Modeling (SEM) using the Smart PLS application. The results of the study show that heuristics do not influence investment decision-making, either directly or through market sentiment. Conversely, overconfidence bias exerts a notable positive impact on investment decision-making, both directly and indirectly through market sentiment. Although investors often utilize heuristics, these do not directly contribute to investment decision-making. Overconfidence bias, which reflects excessive confidence in one's abilities, plays an important role in investment decisions. This study contributes to understanding how biases affect investment behavior and emphasizes the importance of market sentiment in mediating these effects.